A set of polymorphic DNA microsatellites useful in swamp and river buffalo (Bubalus bubalis) - Moore, S S; Evans, D; Byrne, K; Barker, J S F; Tan, S G; Vankan, D; Hetzel, D J S (Wiley, 1995)
DNA microsatellites have found widespread application in gene mapping, pedigree determination and population genetics. In closely related species such as bovids, heterologous polymerase chain reaction (PCR) primers may in some cases be used, bypassing the need to isolate and characterize microsatellite‐containing sequences and design PCR primers. We report on the ability of a set of eighty bovine derived DNA microsatellite primers to amplify sequences in the two types (swamp and river) of water buffalo (Bubalus bubalis). Number of alleles and per cent heterozygosities in a large number of animals were determined on a subset of microsatellite loci selected on the robustness of the primers. These loci will form the basis of a set of polymorphic DNA markers for use in water buffalo. © 1995 International Society for Animal Genetics